Prosthetic rehabilitation of resected orbit in a case of mucormycosis - Harsimran Kaur; Aditi Nanda; Mahesh Verma; Parul Mutneja; Dheeraj Koli; Smiti Bhardwaj (Wolters Kluwer Medknow Publications, 2018)
The design of orbital prosthesis to rehabilitate patients with orbital exenteration depends on the underlying clinical condition, material chosen for prosthesis, method of retention of the prosthesis, and and preference of the patient. Rehabilitation of a patient with orbital exenteration due to mucormycosis has been described by fabricating a prosthesis that used polymethyl methacrylate (to fabricate a conformer) and silicone material (to fabricate prosthetic superstructure). The two-component prosthesis was designed to attain dual mechanical retention using an anatomic undercut (conformer) and manually created mechanical undercut (prosthetic superstructure). The objective was to maintain the biological health of the underlying postsurgical tissue, longevity of the prosthesis, optimal esthetics, and adequate retention.